Effect of rare-earth-based nanoparticles on the erythrocyte osmotic adaptation - Pakulova, O. K.; Klochkov, V. K.; Kavok, N. S.; Kostina, I. A.; Sopotova, A. S.; Bondarenko, V. A. (Biophysical Bulletin)
Rare-earth-based nanoparticles (REB NPs) have been employed in molecular and cell biology due to their unique features. However, their interaction with biosystems and the influence on cell functioning are poorly understood. In this study effect of REB NPs (composed of dielectric nanocrystalls of cerium dioxide and orthovanadates of gadolinium and yttrium) with different form-factor as well as REB NPs-cholesterol complexes on the adaptation of human erythrocytes to hypertonic lysis (4 M NaCl) has been evaluated spectrophotometrically. It appeared that the degree of cell damage in the presence of REP NPs under hyperosmotic conditions varied with geometric parameters of REB NPs. Specifically: i) ultra-small (2 nm) spherical CeO2 or GdYVO4:Eu3+ NPs, penetrating through the plasma membrane, ii) grain-like (8´30 nm) GdVO4:Eu3+ NPs, adsorbed on the membrane surface, iii) and spherical GdYVO4:Eu3+ NPs-cholesterol complexes promoted cell adaptation to hypertonic lysis. Furthermore, the composition of nanoparticles affected their stabilizing effect on the cells. E.g., orthovanadate NPs at 0.1 g/l had the highest antihemolytic activity after short preincubation, while cerium dioxide NPs showed the same effect after prolonged preincubation. In conclusion, REB NPs promoted hyperosmotic cell adaptation by the two different mechanisms, viz. membrane stabilization by the adsorption on the cell surface and/or penetration into the cell.